Determining safety of betacarboclomet cream in epidermal delivery to the body of animals - G. M. Voytenko; Aram Dullah; I. O. Vlasenko; L. L. Davtyan (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. The article is devoted to safety determining of newly developed drug as one of the important stages of preclinical evaluation in the organization of industrial manufacturing.